Kodamaea ohmeri as an Emerging Human Pathogen: A Review and Update - Menglan Zhou; Menglan Zhou; Yanbing Li; Yanbing Li; Timothy Kudinha; Timothy Kudinha; Yingchun Xu; Yingchun Xu; Zhengyin Liu (Frontiers in Microbiology, 2021)
Background:Kodamaea ohmeri, previously known as Pichia ohmeri or Yamadazyma ohmeri, has been regarded as an emerging human pathogen in recent decades, and has caused various types of infections with high mortality. This study systematically reviewed all the published cases of K. ohmeri infection, aiming to have a better understanding of the clinical and epidemiological characteristics of the organism.Methods: All the published literature (as of March 31, 2021) on K. ohmeri, in four databases: PubMed, Embase, Web of Science, and CNKI, were systematically reviewed to select appropriate studies for summarizing the demographic information, clinical and microbiological characteristics of relevant infections.Results: A total of 51 studies involving 67 patients were included for final analysis, including 49 sporadic cases and two clusters of outbreaks. Neonates and the elderly constituted the majority of patients, and fungemia was the dominant infection type. Comorbidities (like malignancy, diabetes, and rheumatism), invasive operations, previous antibiotic use and prematurity, were commonly described in patients. Gene sequencing and broth microdilution method, were the most reliable way for the identification and antifungal susceptibility testing of K. ohmeri, respectively. Amphotericin B and fluconazole were the commonest antifungal therapies administered. The calculated mortality rates for K. ohmeri infection was higher than that of common candidemia.Conclusion: In this study, we systematically reviewed the epidemiology, clinical characteristics, microbiological features, treatment, and outcomes, of all the published cases on K. ohmeri. Early recognition and increased awareness of K. ohmeri as an emerging human pathogen by clinicians and microbiologists is important for effective management of this organism.